The usage of the prescribed forms 1 - 3 English textbooks provided by the education department for teaching English in the lower forms in SMK Tun Abdul Razak; a teacher’s perspective/ Penik Bantok - Bantok, Penik (2003)
This study attempts to seek the teachers* opinions on the usage of the prescribed Forms 1 - 3 English textbooks to teach English language in the lower secondary school, especially in the rural areas. The introductory chapter gives a brief account on the purpose of the study and the significant of the study. Chapter two states the current view from the literature available concerning about the usage of the textbooks. Chapter three describes the research design and methodology for the study. It’s procedures and measuring instrument used. Chapter four discussed about the finding from the questionnaire on the prescribed Forms 1 - 3 English textbooks that were given to 15 English teachers in SMK Tun Abdul Razak. The last Chapter discussed about the summary, conclusion and the recommendation on the usage of the prescribed Forms 1 - 3 English textbooks.